(untitled) (Fiep Bulletin - online, 2014)
The study investigates the Social Representations of Labor Gymnastics among a group of practitioners from the Hygienic cleaning sector in Centro Universitário Feevale, with the objective of identifying how these are revealed, being characterized as a case study. The adopted methodology uses Comprehensive Sociology, inside the qualitative research paradigm, and the data reading and interpretation is made through phenomenology. The researched group was constituted by 8 (eight) collaborators from the Hygienic cleaning sector and the instruments used in the data collection were the half-structuralized interview, the focal group and the participant observation. The theoretical landmark approached: the Social Representations, where we intend to clarify a little of this still recent theory; and the Labor Gymnastics. We evidence that the Labor Gymnastics is very well received by the collaborators, who emphasize all its benefits. We also have to mention its contribution as education for health and quality of life, because of the important role that it represents. We expect that this research may serve as a consultation source to other researchers, as well as stimulation so that a bigger approach between Physical Education and Applied Social Sciences occurs.